2022
DOI: 10.3390/ani12233371
|View full text |Cite
|
Sign up to set email alerts
|

Daily Rhythms in the IGF-1 System in the Liver of Goldfish and Their Synchronization to Light/Dark Cycle and Feeding Time

Abstract: The relevance of the insulin-like growth factor-1 (IGF-1) system in several physiological processes is well-known in vertebrates, although little information about their temporal organization is available. This work aims to investigate the possible rhythmicity of the different components of the IGF-1 system (igf-1, the igf1ra and igf1rb receptors and the paralogs of its binding proteins IGFBP1 and IGFBP2) in the liver of goldfish. In addition, we also study the influence of two environmental cues, the light/da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…Recent work by Alonso-Gomez et al, Mazzoccoli et al, and Chaurdhari et al. revealed IGF-1 levels in the liver and serum exhibit circadian rhythms ( 90 92 ). Additionally, circadian regulation of IGF-1 has been shown to regulate cancer progression in non-small cell lung cancer cells ( 90 93 ).…”
Section: Circadian Modification Of the Tumor Microenvironmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent work by Alonso-Gomez et al, Mazzoccoli et al, and Chaurdhari et al. revealed IGF-1 levels in the liver and serum exhibit circadian rhythms ( 90 92 ). Additionally, circadian regulation of IGF-1 has been shown to regulate cancer progression in non-small cell lung cancer cells ( 90 93 ).…”
Section: Circadian Modification Of the Tumor Microenvironmentmentioning
confidence: 99%
“…Specifically, acute radiation increases expression of IGF1R and secretion of IGF-1, which activates the phosphatidylinositol 3-kinase (PI3K)-Protein kinase B (Akt) pathway to prevent apoptosis and promote survival (88,89). Recent work by Alonso-Gomez et al, Mazzoccoli et al, and Chaurdhari et al revealed IGF-1 levels in the liver and serum exhibit circadian rhythms (90)(91)(92). Additionally, circadian regulation of IGF-1 has been shown to regulate cancer progression in non-small cell lung cancer cells (90)(91)(92)(93).…”
Section: Growth Factor Axismentioning
confidence: 99%
See 1 more Smart Citation